Kép a Képben - Művészeti magazin
editor and presenter Katalin Gopcsa, medieval stone sculptures, Tihany lapidarium, István Fonyó's art collector, exhibition of György Györgydeák, performance by László fe Lugossy and János Szirtes, quiz prizes